HOW INNOVATION ENCOURAGES SELF EFFICACY TO SUPPORT BUSINESS START UP SUCCESS? - Srinathasya Br Sitepu (School of Business, IPB University (SB-IPB), 2017)
A business start up is identical to a new business run by an entrepeneur to gain profit. The research is to analyze the function of the entrepreneurship training given by Universitas Ciputra Surabaya to the villagers in Desa Mojowarno. The objectives of the research are: 1) to learn the proper innovation technique to increase the self efficacy of the entrepreneur/participant, 2) to understand the impact of the increased self-efficacy towards the business continuity managed by the entrepreneur/participant. The research method used is qualitative descriptive analysis with the subject of the research are entrepreneurs (ten training participants) who managed banana trunk chips in Mojowarno. The validation technique used in this research is triangulation data method with participative observation, in depth interview and documentation (photo and video of the participants’ capability). The result of the research: 1) Innovation realization (5+1 concept) succeeded in increasing the self efficacy of the participants (ten training participants); 2) The self-efficacy increase provides a positive impact (business increase) so that the entrepreneur has an additional income. It is suggested that the entrepreneur must keep on innovating innovated to increase their self-efficacy so that the business can improve the continuity.Keywords: descriptive qualitative, innovation, self-efficacy, business entrepreneur start up, trainingABSTRAKStart-up bisnis identik dengan usaha baru yang dijalankan oleh seorang entrepreneur untuk mendapatkan keuntungan. Penelitian ini menganalisis peran pelatihan kewirausahaan yang diberikan Universitas Ciputra Surabaya kepada masyarakat Desa Mojowarno. Tujuan penelitian ini terdiri dari: 1) mengetahui teknik yang tepat untuk berinovasi guna meningkatkan self-efficacy dari entrepreneur/peseta yang mengikuti pelatihan, 2) Mengetahui dampak dari peningkatan self-efficacy terhadap keberlangsungan bisnis yang dijalankan oleh entrepreneur/peserta pelatihan kewirausahaan. Metode penelitian menggunakan analisis kualitatif deskriptif dengan subjek penelitian adalah entrepreneur(sepuluh orang peserta pelatihan kewirausahaan) yang menjalankan bisnis keripik bonggol pisang di Mojowarno. Teknik validasi dalam penelitian menggunakan metode triangglasi data dengan observasi parisipatif, wawancara mendalam, dan dokumentasi (foto dan video kemampuan peserta). Hasil penelitian: 1) Realisasi inovasi(konsep 5+1) berhasil mendorong peningkatan self-efficacy dari entrepreneur(sepuluh peserta pelatihan), 2) Peningkatan self-eficacy memberikan dampak positif(peningkatan bisnis) sehingga entrepreneur(peserta pelatihan) sudah memiliki pendapatan tambahan. Saran bagi entrepreneur harus terus berinovasi untuk peningkatan self-efficacy sehingga peningkatan bisnis terus berlangsung. Kata kunci: kualitatif deskriptif, inovasi, self-efficacy, start-up bisnis,entrepreneur, pelatihan